2020
DOI: 10.3390/insects11090630
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility between Entomopathogenic Fungi and Egg Parasitoids (Trichogrammatidae): A Laboratory Study for Their Combined Use to Control Duponchelia fovealis

Abstract: The European pepper moth, Duponchelia fovealis (Lepidoptera: Crambidae), is a key pest in strawberry production. Entomopathogenic fungi (EF) and parasitoids of the Trichogrammatidae family are effective biological control agents of this pest with the potential to be used jointly for improved efficacy. This study aims to evaluate the susceptibility of Trichogramma atopovirilia and Trichogramma pretiosum to two Beauveria bassiana strains (B2 and B3) and two commercial bioinsecticides (Bovemax® and Methamax®) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…In the end, the 15 isolated strains were classified as B. bassiana (Figure 1). This fungal species has entomopathogenic characteristics and the potential to be used as a biological agent for controlling insect pest populations of different crops, as reported in several studies [9][10][11][12][13]. Further investment in biological control with entomopathogenic fungi could contribute to sustainable crop production either as a stand-alone strategy or in support of other biological and IPM strategies [22].…”
Section: Isolation and Identification Of Entomopathogenic Fungimentioning
confidence: 92%
See 1 more Smart Citation
“…In the end, the 15 isolated strains were classified as B. bassiana (Figure 1). This fungal species has entomopathogenic characteristics and the potential to be used as a biological agent for controlling insect pest populations of different crops, as reported in several studies [9][10][11][12][13]. Further investment in biological control with entomopathogenic fungi could contribute to sustainable crop production either as a stand-alone strategy or in support of other biological and IPM strategies [22].…”
Section: Isolation and Identification Of Entomopathogenic Fungimentioning
confidence: 92%
“…The damage caused by this coleoptera on P. peruviana and the absence of commercial pesticides have led producers and agricultural technicians to seek alternatives [8], which include biological controls [4,9]. In this regard, the search in the wild for natural enemies, such as parasitoids, predators, and entomopathogenic fungi, associated with this coleoptera pest species is crucial for guiding new research on organisms with the potential to be used in conservation biological control strategies or applied biological control programs [4,10,11]. A highly diverse range of entomopathogenic fungi can be naturally present in agroecosystems, acting as regulators of arthropod pest populations [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There also exists the possibility that conidia adhering to G. molesta eggs might reduce their susceptibility to parasitism by the wasp or reduce the fitness of surviving wasp offspring. For these reasons, the potential compatibility of EPFs with egg parasitoids in augmention programs have often been evaluated 33‐36 with a view to optimizing application techniques to avoid any potential adverse effects of the EPF on the parasitoids. An assessment of the potential for intraguild effects and possible antagonistic interactions between B. bassiana and T. dendrolimi is therefore a prerequisite for their joint application in a management program for G. molesta 16,32,37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…ludens [ 13 ]. In another compatibility study, entomopathogenic fungi Beauveria bassiana (two strains) and trichogrammatid parasitoids in genus Trichogramma were evaluated for combined utilization against the European pepper moth Duponchelia fovealis (Zeller), family Crambidae [ 14 ]. Both B .…”
mentioning
confidence: 99%
“…The authors suggested that Beauveria and Trichogramma could be combined to control D . fovealis under natural conditions [ 14 ].…”
mentioning
confidence: 99%